Determination Of Flow Resistance In Modular Open Channel - Kee, Li Choo (2011)
Storage tank module is a lightweight modular system which commonly used as underground storage tank for rainwater harvesting. This storage tank module promotes reuse of rainwater, infiltration of surface water and water quality improvement. In sustainable stormwater drainage system designed by River Engineering and Urban Drainage Research Centre (REDAC), Universiti Sains Malaysia (USM), this storage tank module was used as underground conveyance conduit integrated with grassed swale. There are two types of modular channel investigated in this study which is the existing and newly designed modular channel which is known as Modular Channel Type A and Modular Channel Type B respectively.